Nurses' experience of contesting discourses in HIV/AIDS activities in the primary health care setting - Tutani, Lumka (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
This paper explores the experience of nurses who work both as Primary Health Care Providers and counsellors trained in the narrative model of counselling in primary health care settings. Five focus groups were conducted in both Xhosa and English. Discourse analysis was used as a method of analysing the data. Training nurses in the narrative counselling model introduced an alternative discourse, which was experienced as contradicting their usual way of working. Two dominant discourses were the "not knowing" approach, assumed by the narrative model of counselling, and the "knowing" stance, assumed by health education. The institutionalised construction of counselling by doctors and matrons, and their power versus the power of the nurse counsellors was also cited as sources of conflict. Despite the tensions, narrative model of counselling seems to be offering new positions, which may benefit people living with HIV and improve HIV/AIDS activities in the Primary Health Care (PHC) context.
Keywords: Primary health care; AIDS (Disease) -- Nursing; AIDS (Disease) -- Patients -- Counseling of